SEED TREATMENT IS AN ECOLOGICALLY SAFETY AND EFFECTIVE WAY OF PROTECTING SUGAR BEET SEEDLINGS - Polishchuk Valentin Vasilevich; Balabak Anatolii Fedorovich; Velicho Julya Anatolievna; Pushka Iryna Mykhaylivna; Osipov Mykhailo Yuriiovych; Kozachenko Irina Vladimirovna (Scientific Journal of Pedagogy and Economics, 2019)
Weevils (Bothynoderes punctiventris Germ.) and wireworms (genus Elateridae) cause the greatest damage to the beet growing sector in Ukraine. These pests, with ineffective protection of seedlings, can partially or completely to destroy beet crops. Density and uniformity of plant location decreases with their death and, respectively, sugar beet yield decreases too. Damaged, but living plants lag behind in growth and development which also leads to a decrease in crop productivity. Studies of the effectiveness of protection of shoots from pests in the subzones of sufficient wetting of the beetroot belt in Vinnytsia region (Archi LLC) and in the subzone of unstable moistening Cherkassy region (Verkhnyatsky ESS of the Institute of Bioenergetic crops and sugar beet of the National Academy of Agrarian Sciences (IBCSB NAAS) and Cherkasy SARSNSC "Institute of Agriculture"NAAS)) were conducted. The most effective way to protect shoots of sugar beet from pests and diseases is to create tolerant hybrids, as well as tillage, observance of crop rotations, spraying of shoots with insecticides and fungicides during the vegetation period and application of granular protective preparations to the soil. But the most environmentally safe and effective way - plant toxification when insecticides and fungicides are included in dragees and incrustation mixtures in the process of presowing seed preparation. Research has shown that plant protection chemicals which are less in contact with the soil when seeded with dragee seeds encrusted with protective preparations. The total contact area, depending on the seeding rate, is about 7.03-8.04 m2 per hectare of sugar beet sowing, when applying granular protection product into the soil is 444 m2 , and when spraying the crops is 10000 m2 . That is, the most ecological way to protect the emergence of sugar beet is sowing seeds treated with protective products.